Analisis Regresi Linier Berganda untuk Melihat Pengaruh Budaya Organisasi, Kepemimpinan, Transformasional, dan Motivasi Kerja (Studi Kasus : PT. Telkom Ambon) - H. Lellolsima; M. S. Noya Van Delsen; Yopi Andry Lesnussa (JUSTE (Journal of Science and Technology), 2021)
Human resources are one of the important things in running a company. In this era of increasing competition, both the trade and.service industries. So.the company needs to improve its performance. To improve the performance of the company, it is necessary to have good employee performance. Employee performance can increase if the factors within the company can.affect the performance of the employees themselves. Factors that can affect employee.performance are organizational culture, transformasional leadership, and work.motivation. This research was conducted at.PT. Telkom Ambon using multiple linear regression analysis method. It was found that the employees of PT. Telkom Ambon has an organizational culture, transformational leadership and work motivation that have a positive and significant.effect. The test of multiple linier regression.analysis found that organizational variables, transformational leadership and work motivation can affect employee performance.with a Coefficient of Determination (R2) of 0.832 or 83,2%.